Metabarcoding survey of meroplankton communities in the South China Sea and Philippine Sea: Shedding light on inter-basin biogeography in the West Pacific - Qihang, Li; Yuanming, Chai; Qianwen, Shao; Zaiming, Wang; Wei, Xie; Yadong, Zhou; Dong, Sun; Xiaohui, Xie; Dongsheng, Zhang (Frontiers in Marine Science, 2022)
Planktonic larvae (meroplankton) plays an important role in both benthic and pelagic ecosystems. The meroplankton study of South China Sea (SCS) and Philippine Sea (PS) may be particularly important, where they could serve as vectors for the influx of Pacific species into the East Indies Triangle (global marine biodiversity center). Here, we employed the meta-barcoding method to investigate the geographical distribution pattern of meroplankton among SCS and PS. The efficiency and performance of the metabarcoding method in meroplankton study were also evaluated and discussed, for a better and more reliable interpretation of the current results and improvement of the method. In this study, metabarcoding method was efficient for meroplankton study with high taxonomic resolution and good accuracy. COI against NT database showed the best taxonomy annotation efficiency, followed by 18S1, then 18S4. The SILVA database showed similar effects to the NT database for the two 18S primers. The meroplankton diversity of SCS is higher than that of PS, and both communities are dominated by Polychaeta, Mollusca, Arthropoda and Echinodermata. Meroplankton geographical patterns are significantly different between the two basins due to the different distribution of their benthic individuals, as well as the influence of five key environmental factors (IC, SCM, SST, SSS and DO). Our results suggest that environmental factors and oceanography processes play important roles in shaping the biogeographical distribution pattern of meroplankton species. A unidirectional dispersal pattern of meroplankton between the SCS and the PS was proposed.